“MAY 68 - NOVEMBER 17, 2018”: SAME COMBAT? - Tartakowsky, Danielle (Revista de Historia Social y de las Mentalidades, 2024)
At the end of 2018, the fiftieth anniversary of the events of May-June 1968, a mobilization of breadth called yellow vests has emerged, whose purpose is far from being clear at the time we wrote. During its first weeks of existence, this phenomenon has mobilized the memory of the French Revolution but also that of 1968 as never before in social movements in France since the 1970s. This article proposes to review what has authorized this comparison with the events of May-June 1968, with particular emphasis on the limits of this comparison. For this purpose, it turns on the conquests of May-June of 68, on their traces in the distinguishable memories of the French respondents at the time of their anniversary and the forces mobilized between the years 1970 and 2018. He concludes with some hypotheses that can explain the totally unpublished character of the movement still in progress.